Typology of PAI Teachers: A Review of the Hadith of the Prophet Muhammad PBUH - Hanafi, Irfan; Mutaqqin, Imron; Tursina, Nanik (PT. Anagata Sembagi Education, 2025)
This article examines the typology of Islamic educators based on a review of the hadith of the Prophet Muhammad SAW, focusing on the ideal personality possessed by an educator according to Islamic teachings. The results of the study show that there are four main typologies mentioned in the hadith, namely hayyin (humble), layyin (gentle), qorib (close or sociable), and sahlun (providing convenience). These four qualities not only reflect the noble character of the Prophet PBUH, but also become essential characters for educators in fostering students holistically. These findings also show that in Islamic education, the role of educators includes dimensions as murabbi, mu'allim, mudarris, and mursyid that integrate intellectual, spiritual, and social aspects. In the midst of the challenges of the era of globalization, this typology is relevant to form educators who are not only professionals in teaching, but also role models in morals and personality. This study emphasizes the importance of strengthening the character of educators based on hadith values as part of the humanist and meaningful transformation of Islamic education